The Effect of Marketing Mix on Car Purchase Decisions at Agung Toyota Bengkulu - Tiara Mayang Sari; Suwarni Suwarni; Iswidana Utama Putra (Social Sciences Journal, 2026)
The purpose of this study was to determine the effect of product, price, place and promotion on car buying decisions at Agung Toyota Bengkulu. Researchers use a type of quantitative approach research. The method used is the questionnaire method. The sample used in this study was 125 respondents. The results showed that multiple linear regression showed Y = 16.639 + 0.229 (X1) + 0.159 (X2) + 0.113 (X3) + 0.274 (X4) + 4.202, meaning that there is a positive or unidirectional relationship between product, price, place and promotion on purchasing decisions at Agung Toyota Bengkulu. From the results of the product test (X1) it shows tcount 3.180 > ttable 1.657 and significance 0.002 < ttable 1.657 and significance 0.042 ttable 1.657 and significance 0.016 ttable 1.657 and significance 0.000 2.45, it can be concluded that accepting the hypothesis means that there is a simultaneous influence between product (X1), price (X2) place (X3) and promotion (X4) to the purchasing decision variable (Y) at Agung Toyota Bengkulu. This can be seen at the significance level of 0.000 <0.05.